The Influence of Thermal Comfort on the Quality of Life of Nursing Home Residents - Mendes, Ana (2017)
Funding This work was supported by GERIA Project (www.geria.web node.com): PTDC/SAU-SAP/116563/2010 and a PhD Grant (SFRH/BD/72399/2010) from Foundation for Science and Technology (Fundação para a Ciência e Tecnologia - FCT) through Operational Competitiveness Programme (COMPETE) as part of the National Strategic Reference Framework. SB work was supported by a grant funded by AIRC (Associazione Italiana per la Ricerca sul Cancro).